Safeguarding and personal budgets: the experiences of adults at risk. Issue 3 (30th May 2019) - Aspinal, Fiona; Stevens, Martin; Manthorpe, Jill; Woolham, John; Samsi, Kritika; Baxter, Kate; Hussein, Shereen; Ismail, Mohamed
Abstract : Purpose: The purpose of this paper is to present findings from one element of a study exploring the relationship between personalisation, in the form of personal budgets (PBs) for publicly funded social care and safeguarding. Design/methodology/approach: Semi-structured interviews were conducted with 12 people receiving PBs who had recently been the focus of a safeguarding investigation. Participants were recruited from two English local authority areas and data were subject to thematic analysis. Findings: The analysis identified three main themes: levels of information and awareness; safeguarding concerns and processes; and choice and control. Many of the participants in this small study described having experienced multiple forms of abuse or neglect concurrently or repeatedly over time. Research limitations/implications: This was a small scale, qualitative study, taking place in two local authorities. The small number of participants may have had strong opinions which may or may not have been typical. However, the study provides some rich data on people's experiences. Practical implications: The findings suggest that adults receiving PBs may need information on an ongoing and repeated basis together with advice on how to identify and address poor quality care that they are arranging for themselves. Practitioners need to be aware of the influence of the level of information received and the interaction of organisational or legal requirements when responding to safeguarding concerns when care being supplied tries to reflect the benefits of choice and control. Originality/value: This paper reports original research asking adults with care and support needs about the interaction between two key policies of safeguarding and personalisation.